The Factors Affecting Health Promotion Implementation Relating to Hypertension Diets in the Elderly Families of Banjarmasin - Unja, Ermeisi Er; Tutpai, Gerdtrudis; Rachman, Aulia (KnE Life Sciences, 2021)
Health Promotion is one of the independent nursing interventions that can improve the patients’ and famiies’ ability to handle hypertension. Health workers, especially nurses, are expected to give health promotion advice to elderly hypertension patients. They are therefore required to have a detailed understanding of the dietary factors which can affect this condition. This study uses observational research with a cross-sectional design and questionnaire. The research was conducted between December 2019 and March 2020. There are 30 respondents, selected via purposive sampling, comprised of families with elderly members suffering hypertension and living in the Andai River Area of Banjarmasin. Data analysis used chi-square and logistic regression tests. Univariate analysis showed most of respondents were in early adulthood and had a good knowledge of the subject. The bivariate test showed a significant relationship between age, attitude, occupation and knowledge with the implementation of Health Promotion on the Hypertension diet (p <0.05). Multivariate analysis indicates that knowledge was the most important factor with an OR = 16. Educational interventions concerning health promotion are able to improve the quality of life and the ability of elderly to understand every health information received. Keywords: Elderly Family, Health Promotion, Hypertension Diet